Readiness as a precursor of early implementation outcomes: an exploratory study in specialty clinics - Melanie Livet; Carrie Blanchard; Chloe Richard (Implementation Science Communications, 2022)
Abstract Background Readiness has been identified as an essential precursor of successful implementation. However, evidence supporting its value is sparse. Empirical studies exploring the relationship between the application of readiness interventions, readiness levels, and implementation outcomes are lacking. The purpose of this study was twofold: (1) to evaluate the effectiveness of a readiness intervention (based on increases in readiness levels, changes in early implementation outcomes (i.e., acceptability, appropriateness, feasibility, and intent to adopt), and qualitative insights into the types of perceived outcomes) and (2) to assess the role of readiness as a predictor of these early implementation outcomes. Methods Seven healthcare specialty clinics engaged in a structured process to assess and build readiness for implementing a comprehensive medication management (CMM) service over a 10-month period. A mixed methods approach, which included surveys with healthcare stakeholders at each clinic (N = 27) and interviews with the lead pharmacists (N = 7), was used to evaluate the effectiveness of the readiness intervention (aim 1). Survey data were also used to conduct multiple regression models to assess the role of readiness as a predictor of early acceptability, appropriateness, feasibility, and intent to adopt CMM (aim 2). Results Significantly higher readiness levels, as well as higher scores on acceptability, appropriateness, feasibility, and intent to adopt, were reported as a result of engaging in the readiness intervention. However, upon closer examination, the direction of this association seemed to be dependent on the type of clinic. Qualitative data on the types of perceived outcomes resulting from engaging in the readiness intervention provided further insights into the potential reasons for these findings. Furthermore, post-readiness levels predicted between 44 and 68% of the variance in the early implementation outcomes. When accounting for clinic membership, readiness remained critical for service acceptability, feasibility, and intent to adopt but not for appropriateness. Conclusion These findings provide insights into the relationship between use of a readiness intervention, readiness levels, and early implementation outcomes. Engaging healthcare settings in a readiness intervention was beneficial in ways more complex than a simple positive linear relationship, highlighting the opportunity to broaden its purpose and expand definitions of readiness success. In addition, the importance of readiness levels in predicting early implementation outcomes, while critical, also seems to be highly dependent on context, particularly for appropriateness (fit).